UMPSA and Muslim Care Malaysia collaborate with Pulau Mabul community - Mimi Rabita, Abdul Wahit (UMPSA, 2023)
SEMPORNA, 1 August 2023 - A total of 37 Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Kilau Volunteers supported the Bajau and Bajau Laut communities living around Pulau Mabul in the Kembara Prihatin@Semporna Programme organised by Yayasan UMP with strategic partner, Muslim Care Malaysia (Muslim Care).